Connecting the curriculum through interdisciplinary instruction (National Middle School Association, 1992)
Whereasl, when middle school teachers share a common group of students and have quality time to discuss the special needs, interests and styles of those students, miracles can occur and wehereas, in middle schools, the interdisciplinary team is the organizational unit that facilitates this collaborative planning and teaching and whereas, as middle schools continue to increase in size and complexity, the interdisciplinary team promotes a climate of smallness essential to students success and teacher efficacy, and whereas, departmentalization does not enable teachers from varying subject areas to collaborate regularly nor does it promote the quality of teacher-student involvement essential to the effective middlele school.